High-throughput thermodynamic computation and experimental study of solid-state phase transitions in organic multicomponent orientationally disordered phase change materials for thermal energy storage. (March 2019) - Shi, Renhai; Chandra, Dhanesh; Chien, Wen-Ming; Wang, Jingjing
Abstract: Understanding the behavior of solid-solid phase transformation in phase change materials is crucial to design advanced thermal energy storage materials. It is however challenging to study the complex solid-solid phase transition and predict the optimal composition with reliable performances (such as high energy storage at invariant phase transition temperature) in multi-component systems based on traditional empirical rules. Therefore, the high-throughput computational framework by coupling thermodynamic calculation via CALPHAD (CALculation of PHAse Diagrams) methodology with key experimental validation is firstly proposed for ternary Pentaglycerine-Tris-(hydroxymethyl)-aminomethane-2-amino-2-methyl-1, 3-propanediol (PG-TRIS-AMPL) system. A self-consistent thermodynamic database of PG-TRIS-AMPL ternary system has been firstly assessed and validated by experimental measurements from in-situ X-Ray-Diffraction (XRD) and Differential Scanning Calorimetry (DSC). Using this thermodynamic database via CALPHAD method, the high-throughput calculation has been performed to seek the optimal composition in PG-TRIS-AMPL ternary system. It is found that two optimal ternary compositions in PG-TRIS-AMPL ternary system are designed as PG0.33 TRIS0.07 AMPL0.60 (ΔHmax = 137.5 kJ/kg) during the 1st invariant reaction αAMPL-rich +βPG-rich →δTRIS-rich +γAMPL-rich at 326.5 K (53.35 °C) and PG0.58 TRIS0.069 AMPL0.351 (ΔHmax = 52.44 kJ/kg) during the 2nd invariant reaction γAMPL-rich +βPG-rich →δTRIS-rich +γ'PG-rich at 338.4 K (65.25 °C), respectively. This finding shows the good balance between high latent heat storage and low invariant phase transition temperature at mid-temperature (20–100 °C) application. Also, the present high-throughput computation approach can be extended into other multicomponent systems for various temperature range. Graphical abstract: Prediction of optimal composition that has maximum energy storage in multi-component system via CALPHAD_based high-throughput calculation with key experimental validation.fx1 Highlights: Reassessed AMPL-TRIS binary phase diagram. Firstly proposed the high-throughput screening methodology to develop multi-components phase change materials for thermal energy storage. Firstly performed ternary phase diagram (PG-TRIS-AMPL) supported with present experimental XRD+DSC study. Quantitatively predicted ternary composites with maximum latent heat storage during solid-state order-orientationally disordered phase transformation by CALPHAD.